2016
DOI: 10.4103/0972-5229.182201
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous arterial hemorrhage as a complication of dengue

Abstract: Bleeding complications of dengue hemorrhagic fever such as epistaxis, gum bleeding, gastrointestinal bleeding, hypermenorrhea, hematuria, and thrombocytopenia have been documented. A 49-year-old female presented with complaints of intermittent high-grade fever for the past 4 days, lower abdominal pain and altered sensorium for 1 day. Laboratory investigations revealed severe anemia, mild thrombocytopenia, hypofibrinogenemia, and positive dengue serology. Emergency ultrasound examination of the abdomen revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Different gastrointestinal tract (GIT) symptoms, such as vomiting and abdominal pain, were observed in 32.01% and 29.71% of cases, possibly due to dengue virus-mediated liver injury [12,16]. Bleeding manifestations such as petechiae, GIT bleeding, gum bleeding, and hematuria were observed in 42.89%, 13.18%, 10.25%, and 09.41% of cases, respectively, which could be due to the consequences of thrombocytopenia and imbalance between clotting and the fibrinolysis system [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Different gastrointestinal tract (GIT) symptoms, such as vomiting and abdominal pain, were observed in 32.01% and 29.71% of cases, possibly due to dengue virus-mediated liver injury [12,16]. Bleeding manifestations such as petechiae, GIT bleeding, gum bleeding, and hematuria were observed in 42.89%, 13.18%, 10.25%, and 09.41% of cases, respectively, which could be due to the consequences of thrombocytopenia and imbalance between clotting and the fibrinolysis system [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…These included the eyes (bilateral narrow anterior chamber), pancreas (edema), small and large intestines (small bowel edema, jejunal-ileal and ileocecal intussusception, and edematous appendix), knee (joint effusion), and muscles (thickened psoas, rapidly expanding hematoma in the intramuscular plane of the right lower abdomen). [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Gold standard comparisons and outcome measurements. Comparison of ultrasound examinations against a gold standard was reported in only 9% (n = 16) of studies.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported a significant number of RSH-associated risk factors that generally are divided into two categories, traumatic and non-traumatic ones. Non-traumatic causes of RSH involve various underlying medical conditions such as anticoagulation therapy or infectionrelated coagulation abnormalities [8,9].…”
Section: Discussionmentioning
confidence: 99%